1996
DOI: 10.1007/bf01982684
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization kinetics of acrylic bone cements by differential scanning calorimetry

Abstract: Bone cements arc widely used for the fixation of metallic prostheses in orthopaedics and to form replacements for skull defects in neurosurgery. Acrylic bone cements are based on a mixture of methyl methacrylate (MMA) and a fine powder of polymethyl methacrylate (PMMA).The polymerization of the bone cement occurs in contact with the bone and the prosthesis which act as the boundaries of a bulk polymerization reactor. The kinetic behaviour of the bone cement plays a fundamental role for the final performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, DC values similar to this study were reported in a few other studies. 31,32 This differences in DC can be due to two reasons. First, some values in the literature were reported after times much longer than 1 h. As the DC values in the current study are seen to slowly increase even after 1 h, it is expected that longer measurement times would have resulted in an increase in the reported DC values as well.…”
Section: A Degree Of Conversion (Dc)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, DC values similar to this study were reported in a few other studies. 31,32 This differences in DC can be due to two reasons. First, some values in the literature were reported after times much longer than 1 h. As the DC values in the current study are seen to slowly increase even after 1 h, it is expected that longer measurement times would have resulted in an increase in the reported DC values as well.…”
Section: A Degree Of Conversion (Dc)mentioning
confidence: 99%
“…The residual monomer, and hence the final DC, in bone cements has been measured in the literature using differential scanning calorimetry, [19][20][21] electron-spin resonance, 22,23 gas chromatography, [24][25][26] FTIR, 27,28 and proton nuclear magnetic resonance ( 1 H NMR) spectroscopy. 29,30 Of the techniques mentioned, only the differential scanning calorimeter has been used to track the DC, indirectly based on the exothermic heat released, in real time 31,32 which is useful information for bone cement material researchers working on new formulations. To measure the development of PS and PE in PMMA bone cements, measurement devices have been developed that simulate the clinical use of bone cements for hip implants.…”
Section: Introductionmentioning
confidence: 99%